THE USE OF SNOWBALLING STRATEGY IN TEACHING READING LITERARY TEXTS (SHORT STORIES) - Wahyuni, Sri (Language Circle: Journal of Language and Literature, 2013)
Reading texts for literary experience is different from reading them for information. Actually, there are two general stances (efferent and aesthetic stances) readers may choose when constructing meaning and responding to literature. In the efferent stance the readerÃ¢â‚¬â„¢s purpose is primarily to gain information and analyze the author technique. The emphasis is on recalling, paraphrasing, and analyzing details. In the aesthetic stance the readerÃ¢â‚¬â„¢s purpose is primarily to Ã¢â‚¬Å“live throughÃ¢â‚¬Â the experience presented in the text and to associate the text with personal experience and feelings. The emphasis is on personally connecting with the text as one reads, developing deeper insights into the human experience and responding thoughtfully to the ideas and insights presented. Thus, it is necessary to apply a strategy in teaching reading literary texts. One of useful strategies for comprehending and discussing literary selections is a snowballing strategy. To apply the strategy in teaching reading literary texts, action research is used as a research methodology. This research is carried out in one of the 4th semester classes, literature study program, Semarang State University.